Alle origini dell'estetica fotografica: l'arte per diritto (Mantichora. Italian Journal of Performance Studies, 2020)
The issue of photography’s copyright was addressed several times in the courts and its importance is not limited to questions of historical-legal. En effect different possibilities of theoretical interpretations of the photography’s nature spring from the way it was treated . It is believe necessary to illustrate the problem by displaying some of the most important processes for the conquest of this right.